PCR-RFLP profile of MHC-DRB 3 class II genes in Marwari horses - SHARMA, R C; MEHTA, S C; BANSAL, R S; PATHAK, K M L (The Indian Journal of Animal Sciences, 2011)
Blood samples (24) of Marwari horses were collected and the DNA was isolated. The PCR amplification of MHCDRB3 gene was carried out using LA31 and LA32 primers and a fragment of 309 bp was amplified. The RFLP analysis of ELA-DRB3 locus was carried out in the samples. Digestion with restriction enzyme Hin f 1 resolved homozygous allelic status in 10 (2 fragments of 241 and 68 bp) and heterozygous status in 14 Marwari horses (three fragments of 309, 241 and 68 bp). The ELA-DRB3 fragment was also digested with restriction enzymes Hae III and Rsa I that resolved the fragments of 221 and 88 and 170 and 139 bp with Hae III and fragments of 238 and 71 and 190 and 119 bp with Rsa I. Results revealed that RFLP analysis at this locus using above restriction enzymes has the potential to group the animals into different classes, which may be of great significance from diseases resistance or susceptibility point of view.